Ethical Code in the Public Accounting Profession (Cultura Económica, 2019)
This paper discusses the ethical responsibility that should govern any kind of profession, and focuses on analyzing the ethical code in the public accountant performance. The Code of Professional Conduct of the American Institute of Certified Public Accountants (AICPA) is the primary source of guidance for accountants in public practice, and the article discusses the purposes the code serves. It also analyzes various situations where the code must be appliedand demonstrates the way this is carried out. Finally, the author describes the code’s problems and the way he believes they can be overcome to make the profession more trustworthy.
Keywords: ETHICS; PROFESSIONAL RESPONSIBILITY; PROFESSIONAL ETHICS; CODE OF ETHICS; PUBLIC ACCOUNTANT